Spatial Conditions of Water Regulating Environmental Services - Triana, Neni; Ngudiantoro, Ngudiantoro; Priatna, Satria Jaya (Journal La Lifesci, 2025)
South Sumatra Province has abundant natural resources that support the economy, but uncontrolled development triggers environmental degradation and disaster risks. Sustainable management is needed in accordance with Law No. 32/2009 and PP No. 22/2021. Water regulation environmental services play an important role in maintaining hydrological and ecosystem balance. GIS-based spatial mapping of landscapes, natural vegetation, and land cover is important as a basis for sustainable environmental policies. The research was conducted in South Sumatra Province using secondary data from the Ministry of Environment and Forestry and related agencies. Spatial analysis was carried out based on GIS with an overlay approach to three parameters: land cover (weight 60%), landscape (28%), and natural vegetation (12%). The assessment used the Simple Additive Weighting (SAW) method and produced the Environmental Services Performance Index (IKJLH), which was classified into five categories: very low to very high. The results are visualized in a colored thematic map to show the differences in water regulation performance in each region. The results of the 2023 spatial analysis show that most areas in South Sumatra Province have good water regulation environmental services performance, with a dominance of medium (55%) and high (33%) categories. Ogan Komering Ilir (60.93%), Banyuasin (53.24%), and North Musi Rawas (26.19% very high) are among the best performing areas. In contrast, Palembang City (52.05% low), Empat Lawang, Lahat, and Lubuk Linggau show ecological pressure due to urbanization and land use changes. This condition emphasizes the importance of sustainable environmental management to maintain water regulatory functions in the future.